The Effect Of Using Impromptu Speaking Method Towards Students’ Fluency In Speaking At Eleventh Grade Of SMA Negeri 2 Bukik Barisan - Rahma Wahidha; Reflinda (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2022)
This research was due to discover the effect of using impromptu speaking method toward students’ fluency in speaking. This research is quantitative research and the kind of this research is experimental research. The design of this research is Pre experimental research with one group pretest posttest design. The population of the research was the eleventh grade student at SMAN 2 Bukik Barisan, which consisted two classes. In taking the sample, the researcher used purposive sampling technique, in which IPA class became the sample of the research, which consisted of 15 students. The data were gotten from the students’ speaking test that were given before and after treatment was given. The result of the research indicate that the score of the students’ posttest is higher than the score of the students’ pretest. The mean score of pretest is 59.867 where the mean score of students’ posttest is 69.50. It mean that the impromptu speaking speaking method gave contribution toward the students’ fluency in speaking. In addition to test hypothesis, the t-obtained is 14.61 while t-table on α= 0,05 is 1.761. It mean that the t-obtained is higher than t-table. In other words, the Ha was accepted, which stated that there was significaant effect of using Impromptu Speaking method toward students’ fluency in speaking at the Eleventh grade students of SMAN 2 Bukik Barisan. It can be concluded that, using Impromptu speaking method gives significant effect for students in learning speaking especially in speaking fluency. In short, impromptu speaking method can improve students’ fluency in speaking that the teacher gave for them.